Peningkatan Kesadaran Siswa SDN 34 Terkait Etika Pancasila Melalui Sosialisasi Pentingnya Membuang Sampah Pada Tempatnya - Engrina Fauzi; Elwidarifa marwenny; Agi Ilhamdi, Annisyafitriya Adira Putri, Annisa Maharani, Faril, Riza Rahmadhani, Indri Adelia, Tria (GLOBAL SCIENTS PUBLISHER, 2025)
The formation of environmental awareness, environmental education, social responsibility, and the role of development models are important in forming a responsible future generation. Among the implementations of instilling an attitude of caring for the environment are maintaining and keeping the school environment clean, disposing of garbage in its place, washing hands and using enough water. This method is a form of socialization with the implementation phase of problem identification, planning, target selection, implementation of socialization, active involvement of targets and reflection. The target of this activity is students of SD Negeri 34 Andalas. The output of the activities produced is an increase in student concern for the environment, the cultivation of positive activities both at school and in the surrounding environment. The level of knowledge and skills of students towards instilling an attitude of caring for the environment has increased significantly.